Review of publications related to environmental education and environmental conservation in Latin America, applying the PRISMA methodology - Díaz-Horna, Ítalo (2022)
Advances in scientific development in recent years, and the possibility of publishing digitally, have generated an increase in the number of scientific publications, both in scientific articles onthe multiple scientific topics and in the number of scientific journals. This situation conditions the need to synthesize the existing information from the proposed search strategy. In this work,a systematic review has been carried out using the PRISMA methodology with previously established inclusion and exclusion criteria, attending to an objective answer: What are the scientificresearch articles published in Latin America in the last 10 years that refer to environmental education as a means to environmental conservation? To answer the question, the metasearch enginesScopus, SciELO, Science Direct, Ebsco Host, Google Academic and Redalyc were used, finding 46 published articles in scientific journals and repositories that met the strictly narrow search criteria. The research analyzed the concepts of environmental education and conservation of the environment, concluding that education at all levels is the most important alternative to understand the need and way of addressing relationships with the natural environment in the development of social activity itself.